2016
DOI: 10.1186/s13742-016-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Fish-T1K (Transcriptomes of 1,000 Fishes) Project: large-scale transcriptome data for fish evolution studies

Abstract: Ray-finned fishes (Actinopterygii) represent more than 50 % of extant vertebrates and are of great evolutionary, ecologic and economic significance, but they are relatively underrepresented in ‘omics studies. Increased availability of transcriptome data for these species will allow researchers to better understand changes in gene expression, and to carry out functional analyses. An international project known as the “Transcriptomes of 1,000 Fishes” (Fish-T1K) project has been established to generate RNA-seq tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…Taxonomic Sampling and RNA Sequencing. A total of 131 transcriptomes included in this study were newly sequenced as a part of the Transcriptomes of 1,000 Fishes Project (Fish-T1K) (20). Specimens representing all major lineages of fishes were collected in the field by numerous colleagues around the world (SI Appendix, Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic Sampling and RNA Sequencing. A total of 131 transcriptomes included in this study were newly sequenced as a part of the Transcriptomes of 1,000 Fishes Project (Fish-T1K) (20). Specimens representing all major lineages of fishes were collected in the field by numerous colleagues around the world (SI Appendix, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…To expand currently available genomic resources for fishes, we established an international consortium (20) to sequence transcriptomes sampled from a wide taxonomic diversity (https://db. cngb.org/fisht1k/).…”
Section: This Article Is a Pnas Direct Submissionmentioning
confidence: 99%
“…For example, a supermatrix of 1,110 genes from 22 actinopterygians was assembled to resolve controversies regarding the evolution of the Otocephalan group (Dai et al, 2018). Recently, the international project “Transcriptomes of 1,000 Fishes” (Fish-T1K) (Sun et al, 2016) published a massive phylogenomic analysis including more than 300 fish species (Hughes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With few exceptions, all fish have genes for IgM, IgD, and most for IgT. Representative sequences for the IgT were used to search the Fish-T1K (Sun et al, 2016) repository that contains transcriptome sequences for 124 fish species, shown in Table S3. Additionally, a bibliographic search was carried out since 2005 to identify the different IgT that have been published in teleosts (see Table S2).…”
Section: Resultsmentioning
confidence: 99%